2008
DOI: 10.1097/wnr.0b013e3282f5105a
|View full text |Cite
|
Sign up to set email alerts
|

Sex hormone testosterone affects language organization in the infant brain

Abstract: Using a phonological discrimination paradigm, we show that the brain responses of 4-week-old infants systematically vary as a function of biological sex and testosterone level. Females who are generally low on testosterone demonstrated a clear phonological discrimination effect with a bilateral distribution. In male infants this effect systematically varied as a function of testosterone level. Males with high testosterone showed no discrimination effect, whereas males with low testosterone displayed a discrimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 22 publications
3
43
0
Order By: Relevance
“…In the light of these findings, it is not surprising that the polarities of the pitch MMR and the rule MMR differ across sexes. The observed differences between boys and girls could be mediated by the hormone testosterone, which has been found to negatively impact phonological discrimination abilities in 1-mo-olds (32) and are in line with evidence showing that girls outperform boys in remote dependency learning at later developmental stages (i.e., at 12 mo) (18) and in general verbal abilities during childhood (26,34).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In the light of these findings, it is not surprising that the polarities of the pitch MMR and the rule MMR differ across sexes. The observed differences between boys and girls could be mediated by the hormone testosterone, which has been found to negatively impact phonological discrimination abilities in 1-mo-olds (32) and are in line with evidence showing that girls outperform boys in remote dependency learning at later developmental stages (i.e., at 12 mo) (18) and in general verbal abilities during childhood (26,34).…”
Section: Discussionsupporting
confidence: 57%
“…With respect to our data, this finding would imply that boys' rule learning is indicated by an enhanced neural response to the nonpredicted syllable at a precognitive level, but girls' rule learning takes place at a more cognitive, memory-based level. Regardless of the nature of the underlying neural mechanisms, developmental differences in the polarity of the MMR across sound features have been observed previously (23), and so have sex differences in early sound discrimination (32). In the light of these findings, it is not surprising that the polarities of the pitch MMR and the rule MMR differ across sexes.…”
Section: Discussionmentioning
confidence: 74%
“…Zambrana et al (2012) demonstrated that girls between the ages of 1 year 6 months and 3 years have a significantly higher level of language comprehension than do boys. Another longitudinal study of newborn children showed that girls respond better to verbal stimuli and have better eye contact than boys (Friederici et al 2008;Leeb and Rejskind 2004;Olafsen et al 2006). Eidevald (2009) found that girls attending kindergarten are more linguistically developed than boys.…”
Section: Discussionmentioning
confidence: 99%
“…Research in other areas that may shed light on such a potential connection has been documented in several longitudinal studies in the fields of languages, motivation, mathematics and self-regulation (Friederici et al 2008;Meece and Painter 2008;Silverman 2003;Zambrana et al 2012). These studies demonstrated differences favouring girls.…”
Section: Theoretical Backgroundmentioning
confidence: 95%
See 1 more Smart Citation